Is the Corporate Average Fuel Economy Scheme Effective at Improving Vehicle Fuel Efficiency in a Small-Scale Market? Evidence from Taiwan - Hwa Lin; Yun-Hsun Huang; Jung-Hua Wu (Energies)
This article discusses how the introduction of corporate average fuel economy (CAFE) standards in Taiwan, whose market and industry size are much smaller than those of Europe, the United States, Japan, and China, can effectively improve vehicle energy efficiency. It examines the changes in passenger car energy efficiency under Taiwan’s CAFE framework and evaluates CAFE compliance performance to summarize its impacts and challenges. Observations indicate that the strategically flexible CAFE scheme is indeed more effective than mandatory minimum energy performance standards (MEPS) in encouraging manufacturers to comply through various methods. This approach has ultimately increased the overall average fuel efficiency of Taiwan’s passenger cars by 23.5% since 2012, while maintaining the diversity of vehicle models in the market. However, there are challenges to implementing CAFE in a small market, such as difficulties in introducing and promoting high-efficiency models, limited activity in the CAFE credit market, and the current overly favorable policy design. The design of the CAFE mechanism is crucial not only for benchmarking with larger economies but also for taking into account local market conditions and industrial capabilities. Taiwan’s next phase of CAFE must incorporate multi-dimensional adjustments to achieve higher, potentially net-zero vehicle efficiency targets.